Reliability of an e-PRO tool of EORTC QLQ-C30 for measurement of health-related quality of life in patients with breast cancer: prospective randomized trial - Wallwiener, Markus; Matthies, Lina; Keilmann, Lucia; Sickenberger, Nina; Wallwiener, Stephanie; Feißt, Manuel; Rom, Joachim; Schneeweiss, Andreas (Journal of medical internet research)
Background: Breast cancer represents the most common malignant disease in women worldwide. As currently systematic palliative treatment only has a limited effect on survival rates, the concept of health-related quality of life (HRQoL) is gaining more and more importance in the therapy setting of metastatic breast cancer. One of the major patient-reported outcomes (PROs) for measuring HRQoL in patients with breast cancer is provided by the European Organization for Research and Treatment of Cancer (EORTC). Currently, paper-based surveys still predominate, as only a few reliable and validated electronic-based questionnaires are available. Facing the possibilities associated with evolving digitalization in medicine, validation of electronic versions of well-established PRO is essential in order to contribute to comprehensive and holistic oncological care and to ensure high quality in cancer research. Objective: The aim of this study was to analyze the reliability of a tablet-based measuring application for EORTC QLQ-C30 in German language in patients with adjuvant and (curative) metastatic breast cancer. Methods: Paper- and tablet-based questionnaires were completed by a total of 106 female patients with adjuvant and metastatic breast cancer recruited as part of the e-PROCOM study. All patients were required to complete the electronic- (e-PRO) and paper-based versions of the HRQoL EORTC QLQ-C30 questionnaire. A frequency analysis was performed to determine descriptive sociodemographic characteristics. Both dimensions of reliability (parallel forms reliability [Wilcoxon test] and test of internal consistency [Spearman rho and agreement rates for single items, Pearson correlation and Kendall tau for each scale]) were analyzed. Results: High correlations were shown for both dimensions of reliability (parallel forms reliability and internal consistency) in the patient’s response behavior between paper- and electronic-based questionnaires. Regarding the test of parallel forms reliability, no significant differences were found in 27 of 30 single items and in 14 of 15 scales, whereas a statistically significant correlation in the test of consistency was found in all 30 single items and all 15 scales. Conclusions: The evaluated e-PRO version of the EORTC QLQ-C30 is reliable for patients with both adjuvant and metastatic breast cancer, showing a high correlation in almost all questions (and in many scales). Thus, we conclude that the validated paper-based PRO assessment and the e-PRO tool are equally valid. However, the reliability should also be analyzed in other prospective trials to ensure that usability is reliable in all patient groups. Trial Registration: ClinicalTrials.gov NCT03132506; https://clinicaltrials.gov/ct2/show/NCT03132506 (Archived by WebCite at http://www.webcitation.org/6tRcgQuou). [J Med Internet Res 2017;19(9):e322]